Single-photon emission from single-electron transport in a SAW-driven lateral light-emitting diode - Tzu-Kan Hsiao (Nature Portfolio, 2020)
Electron-spin to photon-polarisation conversion is a promising technology for achieving free-space or fibre coupled quantum transfer. Here, the authors demonstrate acoustically-driven single photons from single electrons, without the need for self-assembled quantum dots, using a SAW-driven lateral n-i-p junction.